2016
DOI: 10.1038/srep35393
|View full text |Cite
|
Sign up to set email alerts
|

Non-destructive determination of Malondialdehyde (MDA) distribution in oilseed rape leaves by laboratory scale NIR hyperspectral imaging

Abstract: The feasibility of hyperspectral imaging with 400–1000 nm was investigated to detect malondialdehyde (MDA) content in oilseed rape leaves under herbicide stress. After comparing the performance of different preprocessing methods, linear and nonlinear calibration models, the optimal prediction performance was achieved by extreme learning machine (ELM) model with only 23 wavelengths selected by competitive adaptive reweighted sampling (CARS), and the result was RP = 0.929 and RMSEP = 2.951. Furthermore, MDA dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
61
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 121 publications
(62 citation statements)
references
References 22 publications
0
61
0
1
Order By: Relevance
“…APX plays a key role in catalyzing the process of detoxifying hydrogen peroxide in plant cells under stressful environmental conditions (Caverzan et al, 2012). Higher levels of APX production in plants have been attributed to their tolerance to water stress (Kong et al, 2016). However, APX activities in the cultivars used in this study were not significantly higher under water stress conditions compared to non-stress conditions, except for cultivar Nerica U4 and Nerica U7.…”
Section: Investigating the Effectiveness Of Selenite On Drought Stresmentioning
confidence: 64%
See 1 more Smart Citation
“…APX plays a key role in catalyzing the process of detoxifying hydrogen peroxide in plant cells under stressful environmental conditions (Caverzan et al, 2012). Higher levels of APX production in plants have been attributed to their tolerance to water stress (Kong et al, 2016). However, APX activities in the cultivars used in this study were not significantly higher under water stress conditions compared to non-stress conditions, except for cultivar Nerica U4 and Nerica U7.…”
Section: Investigating the Effectiveness Of Selenite On Drought Stresmentioning
confidence: 64%
“…Similarly, the rice seedlings emerged from primed seeds manifested significantly lower MDA contents as well as ROIsaccumulation (Hussain et al, 2016). No significant differences in the shoot POD activity were observed among plants grown with Se supply levels from 0 to 2 µM, except at 1 µM Se (Kong et al, 2016).…”
Section: Investigating the Effectiveness Of Selenite On Drought Stresmentioning
confidence: 86%
“…Other features can be extracted from a combination of single wavelengths. Kong et al [14] used NIR hyperspectral imaging to determine the distribution of malondialdehyde, a stress indicator, in rape leaves. They found that an optimal prediction performance for malondialdehyde detection was achieved by an extreme learning machine model with 23 wavelengths selected by competitive adaptive reweighted sampling (CARS).…”
Section: Hyperspectral Cameramentioning
confidence: 99%
“…Oluşan lipit peroksitlerinin hızlıca parçalanmasıyla reaktif karbon bileşikleri oluşur ve bunların en önemlilerinden biri MDA'dır. GSH, SOD, glutatyon S transferaz gibi antioksidan sistemler tarafından bitki hücrelerindeki lipid peroksidasyonu kontrol altında tutulur [36,37]. Farklı dozlarda toprağa uygulanan borik asit konsantrasyonları C. sinensis bitkisinden elde edilen yeşil çay yaprak ekstrelerinde MDA miktarında ilk hasatta düşüşe yol açmıştır.…”
Section: Tartişma Ve Sonuçunclassified